The Existence of Sarimukti TPA and Its Influence on the Social Environment in Elementary Schools - Rohartati, Sri; Maftuh, Bunyamin; Sopandi, Wahyu; Subekti, Eri; Zuhro, Putri Fatimatuz (Studies in Learning and Teaching, 2025)
This study aims to examine the impact of the Sarimukti Final Disposal Site (TPA) on the social environment in three elementary schools located around the site, as well as the perceptions of students, teachers, and parents regarding its impact. The Sarimukti TPA raises concerns about air, soil, and water pollution that can affect the health and well-being of the surrounding community, especially elementary school students. The research uses a qualitative descriptive method with a case study design, involving three school principals, six teachers, twenty students, and three parents as research subjects. Data was collected through interviews, observations, and documentation. The results of the study show that the existence of the Sarimukti landfill has the potential to cause negative impacts on children's health and the social environment of the school and the surrounding community. These impacts affect not only physical conditions but also the social aspects and welfare of students, teachers, and parents. In addition to interactions in the teaching and learning process at school, students' interactions with the surrounding social environment, including physical environmental conditions, also determine the quality of education in primary schools. Thus, the existence of the landfill has a significant impact on the social environment and education in the area.